Electromagnetic Properties of Pyramids from Positions of Photonics - Minin, I. V.; Minin, O. V.; Yue, L. (Russian physics journal, 2020)
The choice of the operating wavelength of electromagnetic radiation is justified for a pyramid considered as an antenna. It is shown that due to the strong dispersion of the refractive index of the pyramid material, there will always be a part of the spectral range, in which the refractive index corresponds to the condition of electromagnetic wave localization (the photonic jet phenomenon). It is shown that the pyramid can simultaneously serve as a transmitting antenna both at the fundamental frequency and at multiple frequencies. Our consideration and approach are not limited only to the shape of the Cheops pyramid and can be generalized to all other shapes of known pyramids. It can be assumed that, despite the difference in the pyramid shapes throughout the world, such structures can play the role of antennas subject to the principle of mesoscale.